2016
DOI: 10.1002/jsfa.8042
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate juice prevents development of non‐alcoholic fatty liver disease in rats by attenuating oxidative stress and inflammation

Abstract: The data obtained in the present study indicate that the regular consumption of PJ can prevent NAFLD even in the presence of the other risk factors such as obesity, hypercholesterolemia, and high energy, fat and sugar intakes. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…Over the last decade, different parts of pomegranate extracts have been shown to prevent the pathological development of NAFLD associated with the regulation of hepatic lipid metabolism . Panchal et al reported that diets supplemented with 0.08% ellagic acid for 8 weeks improved NAFLD and plasma lipid profiles in HFD‐induced Wistar rats.…”
Section: Effects Of Pomegranate On Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, different parts of pomegranate extracts have been shown to prevent the pathological development of NAFLD associated with the regulation of hepatic lipid metabolism . Panchal et al reported that diets supplemented with 0.08% ellagic acid for 8 weeks improved NAFLD and plasma lipid profiles in HFD‐induced Wistar rats.…”
Section: Effects Of Pomegranate On Nafldmentioning
confidence: 99%
“…Reduce serum levels of TC, TG, LDL-C, VLDL-C, and hepatic steatosis [17] 60 ± 5 mL day −1 7 weeks Rats fed a high-fat/sugar diet Reduce hepatic steatosis level Reduce plasma TG level [80] 500 mL day −1 1 week Healthy humans Reduce plasma MDA level [92] 250 mL day −1 12 weeks T2DM patients Reduce plasma MDA level [93] that regulate lipid metabolism in metabolic disorder associated diseases.…”
Section: Days Stz-induced Diabetic Ratsmentioning
confidence: 99%
“…The pathogenesis of NAFLD is associated with metabolic diseases such as diabetes mellitus, hyperlipidemia, and obesity, which are also the main risk factors of cardiovascular disorders (Cicero, Colletti, & Bellentani, ; Patti et al, ). Currently, there is no approved treatment for NAFLD although health promotion strategies and lifestyle modifications are recommended as the primary steps in disease management (Emamat et al, ; Hekmatdoost et al, ; Mokhtari, Poustchi, Eslamparast, & Hekmatdoost, ; Noori, Jafari, & Hekmatdoost, ; Rahimlou, Ahmadnia, & Hekmatdoost, ; Rahimlou, Yari, Hekmatdoost, Alavian, & Keshavarz, ). Over the past few years, numerous studies have been conducted to find plant‐based biological compounds for treatment of NAFLD (Bahrami et al, ; Mofidi et al, ; Saadati et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The earliest stage of NAFLD is hepatic steatosis, characterized by accumulation of TAG in hepatocytes without signs of inflammation and hepatocellular damage (Haas et al, ). Recent reports demonstrated that consumption of PJ or pomegranate extract decreases high‐fat diet‐induced hepatic steatosis by promoting mitochondrial function, as well as by eliminating oxidative stress and inflammation (Noori et al, ; Zou et al, ). In line with the above reports, we found that the PJ consumption significantly decreased the hepatic TAG content in mice.…”
Section: Discussionmentioning
confidence: 99%